Budaya Partisipatif Muslim Indonesia di Media Sosial: Antara Dakwah Kreatif-Kolaboratif dan Distorsi Pesan - Imam, Imam Alfi; Basit, Abdul; Halwati, Umi (Jurnal Komunikasi Islam, 2025)
This article aims to describe the da’wah activities of Indonesian Muslim communities on social media—specifically in producing, distributing, and consuming religious information—amidst the growing trend of Islamophobia and the negative framing of Islamic news in Western mass media. This study employs a literature review approach and utilizes the participatory culture theory proposed by Henry Jenkins to analyze the data. The results of this study indicate that the active participation of Indonesian Muslims on several social media platforms, such as Instagram, TikTok, YouTube, and Twitter, reflects an increase in the creativity of da’wah among Indonesian Muslims. In addition, their active participation in cyberspace represents an effort to build relationships, engage in collaborative da’wah, and formulate identity. However, their activities on social media also have negative impacts—namely, the potential distortion of religious messages, as not all digital da’wah content creators possess the necessary competencies and religious authority.